Space Supporting Africa Volume 1: A Primary Needs Approach and Africa's Emerging Space Middle Powers - Froehlich, Annette; Siebrits, André (Studies in Space Policy,, 2019)
In this book the background and context of Africa's political and socio-economic landscape is presented and unpacked through a primary needs approach which focuses on climate, biodiversity, health, water, education, and space-related capacity building. African theoretical contributions from the International Relations field are discussed, and Africa's new Space Policy and Strategy, along with debates around the establishment of an African Space Agency, are explored. The African International Space Ecosystem is then analyzed, including its dimensions of intra-African space relations and initiatives, African participation in COPUOS, and international space activities, agreements, and initiatives in Africa. The final part is dedicated to the national space infrastructure and activities of African states. .